A Comparative Study of French, British, Dutch, and Russian External Supervisory Agencies of Investigators and Prosecutors within Integrated Criminal-Justice-System - Agus Budianto (Faculty of Law, Universitas Padjadjaran, 2018)
Criminal justice system consists of sub-systems that carry out different tasks and authorities. However, they have the same purpose to implement legal provisions against crimes. The sub-systems cover police, prosecutor, court, and correctional institution. However, in practice, especially in Indonesia, the relation of these sub-systems is not harmonious. It causes legal certainty becoming hard to achieve. One of the solutions is the establishment of supervisory institutions. Nevertheless, in Indonesia, the function of supervisory institution is still unbalanced. Police investigators and prosecutors are stationed at different institutions. The National Police Commission (Kompolnas –Komisi Kepolisian Nasional) and the Prosecutorial Commission (Komjak –Komisi Kejaksaan) are formed by Presidential Regulation, while the Judicial Commission as the Court supervisory institution is formed by the law. A comparison of France, The Netherlands, United Kingdom, and Russian reveals the fact that Police and Prosecutor are under the Ministry of Internal Affairs and the Ministry of Justice. Therefore, the coordination between investigators and prosecutors can be harmonious under one coordination. This study employed a comparison method to observe the supervisory institutions to minimize the practice of judicial corruption in the sub-system. There are two opportunities. The first is to strengthen the main tasks and authorities of Kompolnas and Komjak by changing the existed legislation or establishing new supervisory institution that covering all supervisory functions in the activities of investigation, prosecution, and examination (by the judge) in one legislation.AbstrakDalam sistem peradilan pidana, terdiri dari sub-sub sistem yang menjalan tugas dan kewenangan yang berbeda, namun memiliki tujuan yang sama, yaitu melaksanakan ketentuan perundang-undangan untuk menanggulangi kejahatan. Sub system tersebut, diantaranya Kepolisian, Kejaksaan, Kehakiman dan Lembaga Pemasyarakatan. Namun praktik di Indonesia, bekerjanya sub-sub system tersebut tidak harmonis, sehingga kepastian hukum menjadi sesuatu yang langka. Salah satu faktor bekerja sub-sub system tersebut adalah adanya lembaga pengawasan, namun di Indonesia, lembaga pengawasan tersebut masih timpang. Penyidik polisi dan jaksa penuntut berada pada lembaga pengawasan yang berbeda, yaitu oleh Komisi Kepolisian Nasional (Kompolnas) dan Komisi Kejaksaan (Komjak) yang dibentuk dengan sebuah Peraturan Presiden, sedangkan untuk pengadilan diawasi oleh Komisi Yudisial yang dibentuk dengan Undang-Undang. Perbandingan yang didapat dari negara Perancis, Belanda, Inggris dan Rusia didapat fakta, bahwa Kepolisian dan Kejaksaan berada dibawah Menteri Dalam Negeri dan Kehakiman, sehingga koordinasi antara penyidik dan penuntut dapat harmonis karena berada dibawah satu koordinasi. Metode yang digunakan adalah melakukan perbandingan pada konteks lembaga pengawas dalam sub system peradilan pidana terpadu untuk meminimalisir praktik judicial corruption. Terdapat dua peluang, yaitu memperkuat tugas pokok dan kewenangan Kompolnas dan Komjak di perubahan perundang-undangan atau membentuk lembaga pengawasan baru dengan sebuah Undang-Undang dengan menggabungkan menjadi satu lembaga fungsi pengawasan pada kegiatan penyidikan, penuntutan dan pemeriksaan di pengadilan (oleh hakim).DOI: https://doi.org/10.22304/pjih.v5n3.a7